1994
DOI: 10.1029/94je01862
|View full text |Cite
|
Sign up to set email alerts
|

Bell Regio, Venus: Integration of remote sensing data and terrestrial analogs for geologic analysis

Abstract: Abstract. The geology and surface morphology of Bell Regio (18-42" N, 32-58'' E) are investigated using a combination of Magellan, Venera, and analogous terrestrial data. The properties of surface units are compared to either direct terrestrial analog measurements or to the behaviors predicted by theoretical models. Five major volcanic sources are identified from geologic mapping (Tepev Mons, Neferiiti corona, a large shield volcano east of Tepev, and two small edifices southeast of Tepev). The volcano Api Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…All three volcanoes exhibit some degree of radial fracturing; none have concentric fractures such as those seen at volcanoes in the Galapagos (McBirney and Williams 1969). None of the volcanoes have near-summit diffuse deposits suggestive of pyroclastic activity, as seen at Ushas Mons (Keddie and Head, 1995), volcanoes in Bell Regio (Campbell and Rogers 1994), and volcanoes in central Eistla Regio (McGill 1994).…”
Section: Comparisonsmentioning
confidence: 91%
See 1 more Smart Citation
“…All three volcanoes exhibit some degree of radial fracturing; none have concentric fractures such as those seen at volcanoes in the Galapagos (McBirney and Williams 1969). None of the volcanoes have near-summit diffuse deposits suggestive of pyroclastic activity, as seen at Ushas Mons (Keddie and Head, 1995), volcanoes in Bell Regio (Campbell and Rogers 1994), and volcanoes in central Eistla Regio (McGill 1994).…”
Section: Comparisonsmentioning
confidence: 91%
“…Quantitative analysis has shown that only a few of the brightest flows in venusian flow fields have roughnesses analogous to terrestrial aa (e.g., Campbell 1992, Campbell andRogers 1994). Rougher flows on Venus can be interpreted as block lavas where a thick crust has been broken during flow, fragmented pahoehoe where continued movement of the flow has broken up the crust, or true aa produced from volatile-rich eruptions.…”
Section: Implications Of Flow Texturesmentioning
confidence: 97%
“…Lava flows have been recognised globally, while pyroclastic density currents and fallout deposits are apparently rare or absent. It has proved difficult to determine the nature of these less common volcanic deposits seen in the radar imagery of Venus and confirmation of an explosive origin has so far mostly proved to be controversial (Campbell and Rogers, 1994;Grosfils et al, 2011;Keddie and Head, 1995;McGill, 2000). One recent exception is a proposed pyroclastic deposit known as Scathach Fluctus, identified by Ghail and Wilson (2013).…”
Section: Introductionmentioning
confidence: 97%
“…Submersible studies of the sea floor illustrate that submarine lava flows exhibit a range of morphologic properties similar to those of subaerial pahoehoe (Ballard et al 1979;Fox et al 1988;Gregg and Fink 1995). Furthermore, recent analyses of lava flow margins (Bruno et al 1992(Bruno et al , 1994 and radar backscatter properties (Campbell and Rogers 1994) suggest that pahoehoe flows can be identified on other planetary surfaces.…”
Section: Introductionmentioning
confidence: 92%